La masculinité hégémonique au crible de l’âge - Ingrid Voléry; Simona Tersigni (Genre, Sexualité et Société)
This article intends to revisit the notion of hegemony, increasingly used in the analysis of masculinity (Raewyn Connell). By approaching it from the standpoint of the body practices that are valued in entertainment spaces, our approach also takes into account age as a social construct. We particularly studied the end of childhood, the beginning of the time during which bodies are transformed and forced into the numerous classifications (of sex, sexuality, age) with which they have been associated since the XVIIIth century. This is an analysis of the devices of new assignments of sex and age unfolding in entertainment spaces, but also, the forms of subjectification children demonstrate, which point out important changes both in the nature of the standards of hegemonic masculinity and in the « fractures of power » across whom it fans out.